Increasing diversity of participation in higher education : a case study of the Elsenburg Agricultural Training Institute - Chinasamy-Dampies, Desiree (Stellenbosch : Stellenbosch University, 2025)
Thesis (MPA)--Stellenbosch University, 2024.